Adoption of learning management systems among information technology educators at a rural South African university : an activity systems perspective - Ngandu, Matipa R (School of Education, 2016)
The growth of ICTs in education is a reflection of societal change. The demand for Higher Education Institutions to produce graduates who are equipped for the 21st century is a primary concern to all stakeholders in the education and development system. In as much as there is a drive to adopt emerging educational technologies there needs to be mature research which unpacks adoption. The focus of this research is lecturers and how their perceptions about LMS influence the rate of uptake in the LMS adoption process. It is important to identify the factors which influence lecturer perceptions. Through a qualitative investigative approach on a single case and guided by an Activity Theory framework, this research manages to interpret key sources of tension and contradictions which highlight the factors which influence lecturer perception. It is important to note that structural mandate does not always yield quality results and therefore it is important to establish perceptions held by key stakeholders in the LMS adoption process.